Promoting students' critical thinking through reading strategy instruction in a reading class - K. R. Vinitha Rani (Indonesian JELT, 2016)
This study examined the application of Reading Strategy Instruction (RSI) in a reading class to promote the critical thinking skills of the second language learners. It aims to find out (1) the critical thinking elements in the questions formulated by the participants before the application of RSI, and (2) the critical thinking elements found in the (a) three selected questions, (b) answers, and (c) reflections written by the participants after the application of RSI. This study included sixteen grade 11 participants of a bilingual school in Jakarta, aged between 16 to 18 years old. The participants underwent two stages (1) before the application of RSI, and (2) after the application of RSI. The RSI applied in this study was a modification of Rothstein & Santana’s (2014) “Question Formulation Technique” and Alder’s (2001) comprehension strategies in answering questions. The collected data were analysed by using the modified critical thinking indicators proposed by Mason (1991) and Henri (1992). The results of the study revealed that applying RSI in the reading class was beneficial in promoting the participants’ critical thinking skills. RSI helped the participants to (i) think differently, (ii) use prior background knowledge, (iii) question the facts given in the text, (iv) identify the issues given in the text, (v) give valid solutions to the problem, (vi) connect themselves with the text and the world, and (vii) justify their arguments using valid examples.